Effect of GA, and NAA on Growth and Yield of Seed Potato Crop - BIRBAL,; VINOD KUMAR,; R.K. SINGH,; V.S. KUSHWAH, (Seed Research, 2026)
Efficacy of plant growth regulators (PGR) like GA, and NAA was studied on various plant growth and yield attributes in cv. Kufri Jyoti which ultimately contribute to tuber number and yield. GA, and NAA increased the plant growth characters measured in terms of emergence and plant height. Plant height was significantly higher in GA, treatment over control. Significantly higher total number and weight of tubers were recorded with GA, followed by NAA. Likewise, the GA, treated plants recorded more number and weight of seed size tubers. The plant growth regulator treatments also recorded higher cost benefit ratio over control.